Generation Z Participation in Implementing Ziswaf: The Roles of Literacy, Social Interest, and Religiosity - Lathiefa Rusli; Zulfa Fadillah; Danik Choiriyah Purnomo; Ely Masykuroh (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
The research aims to analyzes the influence of literacy, social interest, and religiosity on Generation Z’s participation in ZISWAF. Generation Z was chosen due to their role in using digital technology and social media, which can enhance management of ZISWAF. Despite Indonesia’s vast ZISWAF potential, participation by Generation Z remains low. This may be due to limited ZISWAF literacy and social and religious factors. The research employs a quantitative approach using a survey distributed to 100 Generation Z respondents in Indonesia, with purposive sampling ensuring participants had relevant ZISWAF knowledge. The results indicate that ZISWAF literacy did not have a significant effect on participation, suggesting that basic knowledge alone is insufficient to motivate involvement. In contrast, social interest showed a positive and significant influence on participation, highlighting the importance of social attitudes in driving engagement. Religiosity did not show a significant impact, possibly due to differences in understanding and applying religious values in daily life. Overall, the combined influence of literacy, social interest, and religiosity significantly affects participation. These findings imply that a comprehensive strategy, which enhances ZISWAF literacy and social attitudes, is necessary to boost Generation Z’s participation in sustainable ZISWAF management.